14.3k views
4 votes
F(x) = square root 3x+7 , g(x) = square root 3x-7

Find (f + g)(x).

User Cryckx
by
4.7k points

2 Answers

4 votes
Your basically building a new equation with the two functions given to you.
(sqrt(3x + 7)) + (sqrt(3x - 7)) = 0

Then just open up the brackets and simplify further.
sqrt(3x + 7) + sqrt(3x - 7)= 0

Nothing to special really happened there, just removed the brackets. Now you move one of the radicals to the other side so you can square the whole equation.
sqrt(3x + 7) = - sqrt(3x - 7)

Then go ahead and square both sides to remove the radical.
3x + 7 = 3x - 7

Now if you kept trying to isolate x, you find that both sides will just cancel each other out and you are left with,
7 = -7

Since that statement isn't true your answer will be that there is no solution to this equation.
x ∈ Ø
User Brian Stamper
by
5.9k points
3 votes

Answer:

The solution is
(f+g)(x)=√(3x+7)+√(3x-7)

Explanation:

We need to find out the
(f+g)(x)

Given functions are :


f(x)=√(3x+7) ........(1)

and
g(x)=√(3x-7) ........(2)

To find out the
(f+g)(x), we need to add f(x) and g(x)

From equation (1) and (2)


(f+g)(x)=√(3x+7)+√(3x-7)

Therefore, the solution is
(f+g)(x)=√(3x+7)+√(3x-7)

User Rusha
by
5.4k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.